Case report: Rare isolated cystic hepatic metastasis of a patient with squamous cell lung carcinoma history and the prognosis - Liu, Chunbao; Chen, Xiaomin; Su, Hang; Xia, Liang; Lu, Diyu (Frontiers in Oncology, 2022)
Cystic hepatic metastasis of squamous cell carcinoma usually develops from necrosis due to insufficient blood supply, yet metastasis initially resembling simple liver cyst is rare. Here we present a case of a patient with squamous cell lung carcinoma history who found an isolated cystic mass in the liver. Historical MR studies indicated that the mass did not exist 12 months ago, and emerged as a small cystic lesion 7 months ago. Radiological findings and tumor markers level suggested metastasis, while 18F-FDG PET/CT showed moderate tracer uptakes in solid parts of the mass. Pathological study after surgery confirmed metastatic squamous cell carcinoma. Chemotherapy plus recombinant human endostatin and sintilimab therapy was employed after surgery, however, the patient developed remote metastasis of osteolytic lesions in humerus bone and thoracic vertebra. Our case indicates that metastasis should be taken into consideration in emerging cystic hepatic lesion with malignant history.